Book review of The Language Management Approach: A Focus on Research Methodology - Liu 刘景珍 Jingzhen; Dai 戴曼纯 Manchun (Círculo de Lingüística Aplicada a la Comunicación, 2020)
The Language Management Approach: A Focus on Research Methodology Lisa Fairbrother, Jiří Nekvapil and Marián Sloboda (eds.). Berlin, Bern, Bruxelles, New York, Oxford, Warszawa,Wien: Peter Lang, 2018 ISBN 978-3-631-65042-4. https://www.peterlang.com/view/title/16980